PENGOLAHAN LIMBAH CAIR KELAPA SAWIT MENGGUNAKAN REAKTOR UAF (UPFLOW ANAEROBIC FILTER) - Purwanto, Djoko (Kementerian Perindustrian, 2013)
The treatment of waste water palm oil industry using UAF reactor. The research purpose was to make a prototype that includes a wast ewater tank, a sedimentation tank and UAF reactor, and then trial the waste water treatment. Filters used were pieces of PVC pipe, and at the bottom of the UAF reactor filled with sludge. To quickly decrease waste water TSS, the sedimentation addition 0.5% PAC (Poly Aluminium Chloride). Acclimatization process doing duration 30 days, and the waste water treatment process at UAF reactor doing duration 24 hours, then doing analyzed the raw waste water quality before and after the processing of the reactor. Results of analysis of wastewater before treatment is pH 7.36; BOD 980 ppm; COD 1960.6 ppm ; TSS 50 89 ppm ; fatty oil 43 ppm; NH3-H 2,80 ppm and N-Total 246.64 ppm. The results of waste water treatment for 24 hours in the UAF reactor is pH 6.64; BOD 28.84 ppm; COD 56.94 ppm; TSS 48 ppm; fatty oils <1 ppm; NH3-N 0.082 ppm and N-Total 11.31 ppm.Keywords: waste water, palm oil, anaerobic, UAF reactor, tube PVC